Automatic control of Hypothalamus-Pituitary-Adrenal axis dynamics. (September 2019) - Özgür Doruk, R.; Mohsin, Ahmed H.
Highlights: Automatic control algorithms aiming at the control of Hypothalamus–Pituitary–Adrenal axis dynamics are presented. The control algorithms are based on back-stepping and feedback linearization techniques. Any reference cortisol profiles can be tracked provided that no negative concentrations are obtained (especially for adrenocortocotropin injection). The main purpose is to maintain a periodic daily rhythm for the cortisol concentration. Application of closed loop control of cortisol concentration can be beneficial where there are irregularities in the adrenocorticotropin secretion such as Cushing syndrome. The daily rhythm of the cortisol is expected to be recovered. Abstract: Background and Objective: In this study, a presentation is made for the automatic control of the hypothalamus-pituitary-adrenal axis which plays an important role in the immune stress responses and the circadian rhythms of mammalian organisms. Methods: Control approaches are implemented on a novel second order nonlinear system which accepts adrenocorticotropin hormone as an input and models the variation of plasma concentrations of adrenocorticotropin and cortisol respectively. The control methods are based on back-stepping and input-output feedback linearization techniques. The controllers adjust the adrenocorticotropin injection to maintain the daily rhythm of the cortisol concentration. In accordance with the periodicity of biological clock mechanism, we provide a sinusoidally varying cortisol reference to the controllers. Results: Numerical simulations are performed (on MATLAB) to demonstrate the closed loop performance of the controllers. Major concerns in the selection of the control gains are chattering and negative concentration in responses. The simulation results showed that one can successfully find gain levels which do not lead to those issues. However, the gains lie in different ranges for back-stepping and feedback linearization based controllers. Conclusion: The results showed that, both back-stepping and feedback linearization based controllers fulfilled their duty of synchronization of the cortisol concentration to a reference daily periodic rhythm. In addition to that, the risk of negative valued adrenocorticotropin injection can be eliminated by properly choosing the controller gains.